(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Factors affecting consumer consumerism Iraqi The research aims to shed light on the factors influencing consumer consumerism Iraqi and arranged in terms of the degree of importance in influencing through poll sample, which amounted to (85) members of the shoppers of electrical goods in the markets of Baghdad, Questionnaire has been used as a tool head to collect data and information from the sample surveyed and their answers were analyzed using factor analysis and test ( ), and The research group was the most prominent